2009
DOI: 10.1261/rna.1626109
|View full text |Cite
|
Sign up to set email alerts
|

Pathology-related mutation A7526G (A9G) helps in the understanding of the 3D structural core of human mitochondrial tRNAAsp

Abstract: More than 130 mutations in human mitochondrial tRNA (mt-tRNA) genes have been correlated with a variety of neurodegenerative and neuromuscular disorders. Their molecular impacts are of mosaic type, affecting various stages of tRNA biogenesis, structure, and/or functions in mt-translation. Knowledge of mammalian mt-tRNA structures per se remains scarce however. Primary and secondary structures deviate from classical tRNAs, while rules for three-dimensional (3D) folding are almost unknown. Here, we take advantag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Reactivities of residues within the variable domain and of residue 26 are compatible with the following triples: G10–C25/A45, A13–U12/A46 and A26–A44. The existence of triple 9/12–23 has been previously supported experimentally, combining a structural and functional mutagenic approach ( 33 ). Only interaction between residues 15 and 48 could not be tested (reactivity of residue 15 is poisoned by a systematic degradation of the 15–16 phosphodiester bond and U48 is not sensitive to the probes used herein).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Reactivities of residues within the variable domain and of residue 26 are compatible with the following triples: G10–C25/A45, A13–U12/A46 and A26–A44. The existence of triple 9/12–23 has been previously supported experimentally, combining a structural and functional mutagenic approach ( 33 ). Only interaction between residues 15 and 48 could not be tested (reactivity of residue 15 is poisoned by a systematic degradation of the 15–16 phosphodiester bond and U48 is not sensitive to the probes used herein).…”
Section: Discussionmentioning
confidence: 88%
“…By analogy to classical tRNAs, only four potential tertiary interactions in the core of the 3D structure would be conserved when the full set of available mammalian mitochondria sequences of tRNA Asp are considered (7,32) (Figure 1B). Among them, the existence of the triple interaction A9/A12-U23 has recently been experimentally confirmed while investigating the effects of myopathy-related mutation A7526G (A9G) on structure and aminoacylation properties of mt-tRNA Asp (33).
Figure 1.Tertiary interaction networks in tRNAs.
…”
Section: Resultsmentioning
confidence: 98%
“…It is suggested that the natural occurring modification m 1 A9, m 2 G10 and Ψ27 are important for correct folding. Queuosine at position 34 in the anticodon loop does likely not contribute to the secondary structure [ 55 ]. ( A , B ) adapted with permission from Motorin and Helm [ 40 ].…”
Section: Figurementioning
confidence: 99%
“…For the latter, a noncloverleaf conformation with a strong resemblance to the aforementioned extended hairpin of tRNA Lys has been proposed (Figure B). Aminoacylation studies in vitro show that transcripts of animal mitochondrial tRNAs are altogether worse substrates than transcripts of canonical tRNAs in the cytosol ,, . These findings imply that such plasticity is a common characteristic of animal mitochondrial tRNAs and that despite a general conservation of the base pairing in stem regions , , the minimal structural characteristics of the cloverleaf may frequently be reached only after certain modification steps.…”
Section: Nanoscale Rearrangements Of Trna As An Effect Of Nucleotide ...mentioning
confidence: 99%